Critical Evaluation of Vertical Stud Integration for Enhancing Blast Resistance in Slabs: A Comparative Analysis with Traditional Reinforcement Methods - Anas S.M.; Al-Dala?ien R.N.; Shariq M.; Alam M. (EDP Sciences, 2025)
Originally rooted in military engineering, blast engineering has transitioned across centuries, from ancient fortifications to modern civil structures and nuclear facilities. Emerging from its historical association with warfare, particularly evident in World War II advancements, the field now encompasses a broader scope, addressing the challenges of protecting civilian infrastructure against blasts, both accidental and intentional. This evolution reflects a continuum of expertise, from ancient defenses to contemporary simulations and materials, ensuring resilience in the face of evolving threats. Slabs serve as indispensable structural elements in construction, crucial for dispersing loads and furnishing essential support as floors, ceilings, or roofs. Their primary function is to ensure structural stability by uniformly distributing weight onto columns and walls, while simultaneously furnishing level surfaces for various activities and augmenting architectural appeal. Nevertheless, owing to their extensive horizontal orientation and substantial surface area, slabs are exceptionally susceptible to explosions, particularly those initiated by direct contact, owing to the rapid fluctuations in pressure and impulse loading they undergo. This research initiative is dedicated to probing the anti-blast capabilities inherent in slabs through an innovative paradigm. The methodology entails the integration of vertical short bars, colloquially referred to as studs, to interconnect the compression and tension layer bars of the slab. These studs are purposed as supplementary reinforcement to bolster the structural robustness and fortitude of the slab against blast-induced forces. By introducing this pioneering design component, the authors endeavour to scrutinize the efficacy of the slab's performance when subjected to a touch-off explosion. The investigation juxtaposes the performance of these fortified slabs against two alternative scenarios: slabs lacking studs bridging the compression and tension layers, and slabs reinforced solely on the tension side?an arrangement corroborated by extant experimental study. The findings reveal that incorporating vertical studs significantly strengthens structural integrity, reduces deformation and stress, and improves energy dissipation and damage response under blast loads. This enhancement is attributed to enhanced shear resistance, increased ductility, and superior load transfer, ultimately reducing damage and enhancing resilience. ? The Authors, published by EDP Sciences.